PENGARUH APLIKASI BERBAGAI JENIS PUPUK KANDANG DAN PUPUK ZA TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH ( Allium ascalonicum) - Beni Syah putra; Irwan Agusnu Putra; Dedi Kurniawan (Agrinula : Jurnal Agroteknologi dan Perkebunan, 2022)
Introduction: The purpose of this study was to determine the effect of applying manure and ZA fertilizer as well as the interaction of manure and ZA fertilizer treatment on the growth and production of shallots (Allium ascalonicum L).Materials and Methods: : This research was conducted in Tunggurono Binjai Timur District, North Sumatra from October 2021 to January 2022. The research design is a Randomized Group Design (RAK) with two factors. The first factor with 4 levels: P0 = No Manure, P1 = Cow manure 272.25 gr, P2 = goat manure 272.25 gr and P 3 = Chicken manure 272.25 gr and the second factor with 4 levels: Z0 = No ZA Fertilizer, Z1 = 2.90 gr/polybag, Z2 = 5.8 gr/polybag and Z3= 11.6 gr/polybag. Results: The results showed that the application of manure had a noticeable influence on several parameters at the age of 30 HST. Meanwhile, the ZA fertilizer treatment has an unreal effect on several other parameters and observations. And the interaction of the two has an unreal effect, the best interaction is obtained on the treatment ( P2Z1). Keywords : Organic manure, ZA fertilizer, shallots